تعليم البلاغة وسـيلة لمعـرفة ما في النصوص الأدبية والإعجاز القرآني - Faruq, Umar (Didaktika Religia, 2013)
The article presents the essence of balagah and its development as a means to understand literary texts and figures of speech of al-Qur’an. The main goal is to develop the sense of a language, and finally sense what literary writers have sensed. In this instance, balagah has undergone two developmental stages. The first generation was around 3-4 H, from al-‘Asykari, al-Jahizh, Ibnu al-Mu’taz, Ibnu Qutaibah to ‘Abd al-Qahir al-Jurjaniy at the end of 5 H. at that time, balagah was integrated with the literary works, in the form of both prose and poetry. However, since al-Sakkaky with his al-Miftah, balagah was scientific and logical so that sense of a language was not achieved. Balagah was not then a means but the goal. The consequence is that it does not touch the heart of literary works.